Do Migrants Send Remittances as a Way of Self-Insurance? Evidence from a Representative Immigrant Survey - Catia Batista; Janis Umblijs (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
Do migrants send remittances as a way of obtaining insurance? While this motive is theoretically suggested in the literature, the question of identifying this relationship empirically has only begun to be explored. Using a unique representative survey of 1500 immigrants in the Greater Dublin Area, Ireland, we find a positive and significant relationship between risk aversion and remittance behavior. Risk-averse individuals are more likely to send remittances home and are, on average, likely to remit a higher amount, after controlling for a broad range of individual and group characteristics. Consistent with a "purchase of self insurance" motive to remit, we also provide evidence of more remittances sent by risk averse immigrants facing higher wage risks and remitting to individuals with more financial resources.
Keywords: D81; F22; F24; J01; J08; J15; J61; 330; Migration; Risk Aversion; Remittances; Insurance